Planning transport infrastructure: examining the politics of transport planning in Melbourne, Sydney and Perth. Issue 1 (2nd January 2017) - Legacy, Crystal; Curtis, Carey; Scheurer, Jan
Abstract: Australian cities have observed a "consensus turn" expressed as broad public support of greater accessibility and public transport provision as revealed in metropolitan strategic plans. In contrast large-scale road projects proposed to traverse the inner-city of three major Australian cities reveals an ongoing and deep-seated attachment by some to car-based travel in Australian urban transport planning. Comparative case studies of these three road projects in Melbourne, Sydney and Perth explores the impact that an antagonistic relationship between the state and community has on the culture of transport planning. Through observational insights, policy and media analysis and interviews with community groups, we show that this antagonistic planning culture arises when there is a fracture between metropolitan strategic plan-making and project planning, and when clear channels of communication and deliberation are undermined.